1996
DOI: 10.1002/jpln.1996.3581590613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil properties and cultivar on cadmium accumulation in wheat grain

Abstract: The food industry faces the problem of soil contamination and consequently the deterioration of the quality of plant products. Here, we present a study on evaluation of the effect of fertilization with sewage sludge (SL) with varying, rates of biochar (BC 2.5, 5 and 10% of DW) on yield quality and the accumulation of heavy metals in wheat grains. The greatest grain yield with the highest content of protein and gluten as well as the highest total content of phenols and flavonoids, was obtained when SL+5%BC fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 10 publications
1
22
1
Order By: Relevance
“…Further exceptions are Cu in winter wheat (1.6), Na in winter wheat and durum (up to 2.7) and Sr in winter wheat and durum (up to 1.9) and potatoes (2.0), as well as Co (2.0) in the latter crop. The detected variations of Cd in different cultivars are comparable with those found by Wenzel et al (1996) in winter wheat and spring durum. A total of 22 different cultivars showed differences in the Cd uptake up to a factor of 2.5.…”
Section: Element Concentrations In Different Cropssupporting
confidence: 86%
See 1 more Smart Citation
“…Further exceptions are Cu in winter wheat (1.6), Na in winter wheat and durum (up to 2.7) and Sr in winter wheat and durum (up to 1.9) and potatoes (2.0), as well as Co (2.0) in the latter crop. The detected variations of Cd in different cultivars are comparable with those found by Wenzel et al (1996) in winter wheat and spring durum. A total of 22 different cultivars showed differences in the Cd uptake up to a factor of 2.5.…”
Section: Element Concentrations In Different Cropssupporting
confidence: 86%
“…However, Cd was also amongst the group of elements that were highest in durum wheat. Elevated Cd concentrations in spring durum cultivars have also been described by Wenzel et al (1996). Comparing the two bread grains wheat and rye, it can be stated that the concentrations of P, Mg, Ca, Fe, Zn and Mn were significantly higher in wheat compared to rye.…”
Section: Element Concentrations In Different Cropsmentioning
confidence: 86%
“…E.g., large genotypic variation of Cd accumulation was found for maize shoots (Kurz et al 1999, Florijn 1993, where two main groups of inbreds were distinguished: a group with low shoot, but high root Cd contents (shoot Cd excluder) and a group with similar shoot and root Cd concentrations (non-shoot Cd excluder). Among Austrian wheat cultivars, a 2.5-fold variation of Cd concentration in grain was observed (Wenzel et al 1996). Similarly, a 2.3-fold variation in seed Cd concentration was reported for 17 Australian lineseed lines (Hocking and McLaughlin 2000).…”
Section: Crop Rotation and Growing Of Industrial Cropsmentioning
confidence: 59%
“…In the case of chamomile, sowing in spring yielded higher Cd contents in the flower heads than when the sowing was done in autumn [22]. In trials with various wheat cultivars, Wenzel et al [23] observed that Cd availability for the plants was governed by Cd in the soil and was modified by sorption to organic matter and the concentration of Ca and Cl in the soil solution. To avoid Cd accumulation in wheat, they proposed a careful choice of the variety and adjusting the soil chemical conditions.…”
Section: Toxic Heavy Metalsmentioning
confidence: 99%